2012
DOI: 10.5923/j.cmd.20120202.01
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Poor Prognosis in Patients with Malignant Ascites: A Prospective Study

Abstract: Malignant ascites is a manifestation of end stage events in a variety of cancers with significant morbidity and a poor prognosis.This study prospectively evaluated factors predicting poor prognosis in patients with malignant ascites. Clinico-pathologic data of patients with malignant ascites at our institution over a period of 18 months were prospectively analysed. Predictors of poor survival were evaluated and survival compared among different cancer groups. A total of 150 patients (96 females, 54 males) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…We present very detailed characteristics of a cohort of 180 patients, and our results correlate with smaller prior studies 7,8,25,28–30 that show that ascites is a late manifestation of advanced pancreatic adenocarcinoma, and its presence carries an ominous prognosis, with observed mean OS in our cohort being 12 months (range, 10–14 months [95% CI]) from diagnosis and 1.8 months (range, 1.6–2.3 months [95%CI]) OS after ascites developed. Patients who presented with metastatic disease developed ascites 7 months following diagnosis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We present very detailed characteristics of a cohort of 180 patients, and our results correlate with smaller prior studies 7,8,25,28–30 that show that ascites is a late manifestation of advanced pancreatic adenocarcinoma, and its presence carries an ominous prognosis, with observed mean OS in our cohort being 12 months (range, 10–14 months [95% CI]) from diagnosis and 1.8 months (range, 1.6–2.3 months [95%CI]) OS after ascites developed. Patients who presented with metastatic disease developed ascites 7 months following diagnosis.…”
Section: Discussionsupporting
confidence: 83%
“…Prior studies have evaluated malignant ascites in different types of cancers, 7,8,25,28–30 but very limited data exist on the prognostic importance of malignant ascites in pancreas adenocarcinoma. We present very detailed characteristics of a cohort of 180 patients, and our results correlate with smaller prior studies 7,8,25,28–30 that show that ascites is a late manifestation of advanced pancreatic adenocarcinoma, and its presence carries an ominous prognosis, with observed mean OS in our cohort being 12 months (range, 10–14 months [95% CI]) from diagnosis and 1.8 months (range, 1.6–2.3 months [95%CI]) OS after ascites developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported similar associations between MRA and type of cancer; however, relative percentages and order of frequencies were different. 4,7 For example, in a retrospective study of 209 patients with cancer, MRA was most commonly seen in ovarian (38%), pancreaticobiliary (21%), gastric (18%), esophageal (4%), colorectal (4%), and breast (3%) cancer. 4 The greater proportion of female patients observed in our study was also seen in another smaller study that reported 140 (67%) females of 209 MRA hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although there are some studies evaluating the effects of clinical factors on hospital length of hospital stay and in-hospital mortality among a limited number of patients with MRA, detailed, large database, and epidemiological analyses are lacking, especially at the national level. 4,7,8 In this study, we tried to understand the epidemiology and inpatient hospital outcomes of patients with MRA in the United States using a national database.…”
Section: Introductionmentioning
confidence: 99%